Using position, velocity, and acceleration relationships to assess exercise specificity: a simple tool for the strength coach toolbox - Harry, J. R.; Hite, M.; Simms, A.; Park, S.; Stewart, M.; Barker, L. A. (Strength and Conditioning Journal, 2025)
Training specificity using the dynamic correspondence approach is effective for athletic development because it emphasizes specific movement outcomes and influential strategies. Unfortunately, limited technological resources and formal training can restrict strength and conditioning or sport science professionals from applying research-driven data acquisition and interpretation approaches, creating a reliance on qualitative approaches to assess specificity. However, the dynamic correspondence form of specificity is rooted in mechanics, meaning coaches can often reframe their focus to the motions and accelerations occurring at the joint or whole body (i.e., center of mass) level. These motions can be observed for target exercises, which are the ones we hope to improve during testing or performance, and for the potential training exercises. From those observations, practitioners can create a profile using simple sketches and an understanding of the conceptual relationships among position, velocity, and acceleration (PVA). The article explains the conceptual PVA relationships and demonstrates the PVA profiling process for 2 exemplar scenarios. The simplicity of the PVA profile can provide an additional approach for identifying sport-specific exercises or even within-exercise qualities, such as time periods with high or low acceleration. Strength and conditioning professionals may benefit from supplementing current approaches to specificity determinations with PVA profiles.